The Causal Relationship of Risk in Accounting and Finance, Firm Internal Management, and Firm Performance within Supply Chain of Automotive and Automotive Parts Industry in Thailand: ความสัมพันธ์เชิงสาเหตุระหว่าง ความเสี่ยงทางบัญชีและการเงิน การจัดการภายในองค์การ และผลการดำเนินงานห่วงโซ่อุปทานของกลุ่มอุตสาหกรรมยานยนต์ และชิ้นส่วนยานยนต์ในประเทศไทย - Pichayasupakoon, Tiyadah; Wanarat, Sawat (Journal of Applied Economics and Management Strategy, 2020)
บทคัดย่อ การวิจัยในครั้งนี้มีจุดมุ่งหมายเพื่อ 1) ตรวจสอบความสอดคล้องของรูปแบบความสัมพันธ์เชิงสาเหตุระหว่างความเสี่ยงทางบัญชีและการเงิน การจัดการภายในองค์การ และผลการดำเนินงานห่วงโซ่อุปทาน กับข้อมูลเชิงประจักษ์ และ 2) ศึกษาอิทธิพลทางตรง อิทธิพลทางอ้อม และอิทธิพลรวมระหว่างความเสี่ยงทางบัญชีและการเงิน การจัดการการในองค์การ และผลการดำเนินงานห่วงโซ่อุปทาน ในอุตสาหกรรมยานยนต์และชิ้นส่วนยานยนต์ในประเทศไทย กลุ่มตัวอย่างในการศึกษาครั้งนี้คือองค์การในอุตสาหกรรมยานยนต์และชิ้นส่วนยานยนต์ไทย จำนวน 334 ตัวอย่าง เก็บข้อมูลโดยใช้แบบสอบถาม สถิติที่ใช้ในการวิเคราะห์ข้อมูลประกอบด้วย สถิติเชิงพรรณนา การวิเคราะห์องค์ประกอบเชิงยืนยัน และการวิเคราะห์โมเดลสมการโครงสร้าง ผลการศึกษาโมเดลสมการโครงสร้าง พบว่าโมเดลมีความสอดคล้องกับข้อมูลเชิงประจักษ์ และผลการศึกษาอิทธิพล พบว่า ความเสี่ยงทางบัญชีและการเงินมีอิทธิพลเชิงบวกต่อผลการดำเนินงานห่วงโซ่อุปทานและการจัดการภายในองค์การ นอกจากนี้ ความเสี่ยงทางบัญชีและการเงินยังมีอิทธิพลทางอ้อมเชิงบวกต่อผลการดำเนินงาน ห่วงโซ่อุปทานผ่านการจัดการภายในองค์การ คำสำคัญ: ความเสี่ยงทางบัญชีและการเงิน การจัดการภายในองค์การ ผลการดำเนินงานห่วงโซ่อุปทาน และกลุ่มอุตสาหกรรมยานยนต์และชิ้นส่วนยานยนต์ Abstract The aim of this study is to: 1) examine the causal relationship of risk in accounting and finance, firm internal management, and firm performance within supply chain with empirical data and 2) study the direct influence, indirect influence, and total influence between risk in accounting and finance, firm internal management, and firm performance within supply chain of automotive and automotive parts industry in Thailand. The sample was chosen from companies in automotive parts manufacturing industry in Thailand. The questionnaires were distributed to 334 respondents. The statistics employed in the research were descriptive statistics, confirmatory factor analysis and structural equation model. The results showed that the conceptual model aligned with the empirical data. The findings of this research indicated that risk in accounting and finance has a positive influence on firm performance within supply chain and firm internal management. In addition, risk in accounting and finance has a positive indirect effect on firm performance within supply chain through firm internal management. Keywords: Accounting and Financial Risk, Firm Internal Management, Supply Chain Performance, Automotive and Automotive Parts Industry